Novel velocity and call duration support for QoS provision in mobile wireless networks. - Islam, M.M (IEEE Wireless communications)
This article presents a novel mobility-based resource reservation and call admission control scheme that is applicable to any real wireless multimedia network. The scheme exploits three key mobility parameters - the position, direction, and speed of a mobile unit - together with the duration of a particular call to accurately estimate the cell visiting probability in order to identify a shadow cluster of cells the unit is most likely to visit. Each cell in the cluster reserves resources for an estimated time interval, which is adapted depending on the aggregated probability of all active units visiting a particular cell. Simulation results confirm the superiority of the new scheme over the existing predictive mobility support scheme in terms of three QoS parameters: call blocking rate, call dropping rate, and channel utilization.